For a characterization of detached textual constituents as parenthetic comments based on a modular perspective of the discourse organization - Cunha, Gustavo Ximenes (2021)
For Decat (2011), the unattachment of constituents corresponds to structures that occur freely, without being syntactically linked to a clause or any other textual portion. In this paper, we show that constituent unattachment can be studied in the framework of the Modular Approach to Discourse Analysis. More specifically, we extend to the study of unattached constituents Roulet’s (2004) proposal for the treatment of parenthetic constituents. In this paper, we will study the phenomenon of unattachment in three stages. In the first, we will study the textual relationship that links an unattached constituent to information previously expressed in the text. In the second step, we will analyze the action relation that articulates the unattached constituent to the previously performed actions. Finally, the third stage studies unattached constituents from the point of view of the operational organization form. In this last stage, the results of the previous stages will be combined to understand the discursive motivations of the unattachment. In the different stages, the unattached constituents that we will analyze were extracted from media texts, such as reports and opinion articles.